Exploring the environment, discovering learning resources and creating low cost training and development - Part 1 - Elkin, Graham (Cranfield University, 1990)
Most trainers believe they have insufficient budget to do all that needs to be done to develop the people and organisation for which they work. That feeling is not confined to small businesses or to any particular sector. It is widespread. It can lead to sense of powerlessness to achieve anything at all in the face of the many opportunities which cannot be taken. The problem may be shortage of cash or corporate commitment. It may also be a lack of understanding by the trainer of how much can be achieved by good use of opportunities and resources not automatically seen as relevant to training. This paper suggests some orientations which can lead to greater productivity in training however few the resources under a trainers control. A clearly cost-effective contribution to the bottom line results of an enterprise often leads to an expansion of the contributing activity. If as a result of the changes in training orientation more is achieved, more resources may flow towards training. A systematic model is suggested as the basis for searching for existing non-training resources that can be turned into learning opportunities to augment the investment in training. Some practical examples illustrate the way these approaches can add to the training effort by creating low cost but effective learning experiences.